OCIOSIDADE FABRIL PELOS MÉTODOS UEP E TDABC: VALORES MONETÁRIOS DIFERENTES PARA VOLUMES DE HORAS OCIOSAS IGUAIS? - Wernke, Rodney (2022)
To determine whether the measurement of factory idleness by two costing methods based on production time leads to different monetary values, even with equal idle hours volumes, this research aimed to compare factory idleness by the UEP and TDABC methods in these two parameters in the context of a feed industry. Methodology with a qualitative approach, descriptive typology and the case study procedure were used. The results showed that by the UEP method, the cost of idleness totaled R$ 4,485.18 and by the TDABC, the total value of R$ 3,789.14 was reached, even with equal levels of idleness in the sectors in terms of UEPs not used in the productive potential ( in the case of the UEP method) and unconsumed minutes of the practical capacity installed under the TDABC. Thus, the main contribution refers to the conclusion that there can be equality in the volume of idleness identified in each sector by the UEP and TDABC methods and, concomitantly, different monetary values ​​according to the costing methodology adopted.